Perceived barriers and facilitators to goals of care discussions in the emergency department: A descriptive analysis of the views of emergency medicine physicians and residents. Issue 2 (8th May 2018) - Argintaru, Niran; Quinn, Kieran L.; Chartier, Lucas B.; Lee, Jacques; Hannam, Paul; O'Connor, Erin; Steinberg, Leah; Ovens, Howard; McGowan, Melissa; Vaillancourt, Samuel
Abstract: Objective: Few studies have examined the challenges faced by emergency medicine (EM) physicians in conducting goals of care discussions. This study is the first to describe the perceived barriers and facilitators to these discussions as reported by Canadian EM physicians and residents. Methods: A team of EM, palliative care, and internal medicine physicians developed a survey comprising multiple choice, Likert-scale and open-ended questions to explore four domains of goals-of-care discussions: training; communication; environment; and patient beliefs. Results: Surveys were sent to 273 EM staff and residents in six sites, and 130 (48%) responded. Staff physicians conducted goals-of-care discussions several times per month or more, 74.1% (80/108) of the time versus 35% (8/23) of residents. Most agreed that goals-of-care discussions are within their scope of practice (92%), they felt comfortable having these discussions (96%), and they are adequately trained (73%). However, 66% reported difficulty initiating goals-of-care discussions, and 54% believed that admitting services should conduct them. Main barriers were time (46%), lack of a relationship with the patient (25%), patient expectations (23%), no prior discussions (21%), and the inability to reach substitute decision-makers (17%). Fifty-four percent of respondents indicated that the availability of 24-hour palliative care consults would facilitate discussions in the emergency department (ED). Conclusions: Important barriers to discussing goals of care in the ED were identified by respondents, including acuity and lack of prior relationship, highlighting the need for system and environmental interventions, including improved availability of palliative care services in the ED. RÉSUMÉ: Objectif: Peu d'études portent sur les difficultés que rencontrent les urgentologues dans les discussions sur les objectifs de soins. Il sera donc question dans le présent article, et ce pour la première fois, de facteurs favorables et défavorables à la tenue de ces discussions, tels qu'ils sont perçus par les médecins et les résidents en médecine d'urgence (MU) au Canada. Méthode: Une équipe composée d'urgentologues, de médecins en soins palliatifs et d'internistes a élaboré un questionnaire d'enquête comprenant différents types de questions : à choix multiple, à échelle de Likert ou encore à réponse libre, et portant sur quatre champs relatifs aux discussions sur les objectifs de soins : la formation, les communications, l'environnement et les croyances des patients. Résultats: Le questionnaire a été envoyé à 273 membres du personnel et résidents en MU dans 6 services et, sur ce nombre, 130 (48 %) ont participé à l'enquête. Les membres du personnel médical ont indiqué tenir des discussions sur les objectifs de soins plusieurs fois par mois ou plus de 74, 1 % (80/108) du temps contre 35 % (8/23) des résidents. La plupart des répondants étaient d'accord sur le fait que les discussions sur les objectifs de soins relevaient de leur champ de pratique (92 %), qu'ils se sentaient à l'aise avec ces discussions (96 %) et qu'ils étaient bien formés à cet effet (73 %). Toutefois, 66 % d'entre eux ont indiqué avoir de la difficulté à amorcer les discussions sur les objectifs de soins et 54 % étaient d'avis que celles-ci devraient se tenir dans les services d'admission. Les principaux facteurs défavorables à la tenue de ces discussions étaient le manque de temps (46 %), le manque de relations avec les patients (25 %), les désirs des patients (23 %), l'absence de discussions antérieures (21 %) et la difficulté de joindre les mandataires (17 %). Enfin, 54 % des répondants ont indiqué que la tenue possible de consultations en soins palliatifs, 24 h sur 24, faciliterait les discussions au service des urgences (SU). Conclusions: D'après les répondants, il existe des facteurs défavorables importants à la tenue de discussions sur les objectifs de soins au SU, notamment le degré de gravité des maladies et l'absence de relations antérieures, d'où la nécessité d'élaborer des interventions touchant au système et à l'environnement, dont une disponibilité accrue des services de soins palliatifs au SU.